Perguruan Tinggi Dalam Era Globalisasi: Perspektif Balance Scorecard - Walean, Ronny Hansje (JBE (Journal of Business and Economics); Volume 8 No.2, 2009 JBE UNKLAB, 2009)
The term "Globalization” has acquired considerable emotive force. Some view it as a process that is beneficial – a key to future world economic development. Others regard it with hostility, even fear, believing that it -increases inequality within and between nations, threatens organization, employment, living standard and progress. The crisis in the emerging -markets have made it quite evident - -that opportunities of globalization do not come without risks. -Companies- can survive from a4een -competition by carefully using best methods to. evaluate companies performance so that decision can be implemented effective and efficiently. Balanced scorecard is on of the. alternatives that provides- top. management with the instrument to navigate the future competitive success. The balances scorecard evaluates organization performance in four balanced perspectives: customer, financial, internal business processes, and learning and growth.